Transfer efficiency enhancement on wireless power transfer using metamaterial - Yusri, Muhammad Sukriyllah; Misran, Mohamad Harris; Yusop, Norbayah; Said, Maizatul Alice Meor; Othman, Mohd Azlishah; Suhaimi, Shadia (2023)
Wireless power transfer (WPT) has lately seen significant innovation and development; consequently, there is an ever-increasing need for high power transfer efficiency (PTE) of WPT systems, as well as increased transmission distance for end-users. Due to their use of inductive coupling, a few of the currently available WPT systems have a limited PTE and transmission distance. The PTE suffers a substantial decrease when the distance between the transmitter and receiver coils increases while using this approach. Therefore, this paper proposes metamaterials (MTMs) based inductive WPT design to enhance PTE by manipulating the magnetic field refraction. Inserting MTMs between the transmit (Tx) and receive (Rx) coils increases the efficiency of WPT and the distance. MTMs have evanescent wave amplification and negative refractive qualities properties, both of which have the potential to be used to enhance PTE. At distance, d equal to 70 mm, implementing MTMS is able to improve the PTE with 180% increments. This research is intended to provide insight on the evolution of MTM-based WPT systems.